THE LEGALITY OF CRYPTOCURRENCY (ASET KRIPTO) AS A WAQF ASSET: A CONTEMPORARY ISLAMIC LAW ANALYSI - Hubbul Wathan; Aisha Al Suwaidi; Miriam Hofer (Sharia Oikonomia Law Journal, 2025)
The rapid growth of digital finance has introduced cryptocurrency as a novel asset class, raising profound legal and ethical questions within the framework of Islamic law. The emergence of crypto-based endowments (waqf) has sparked debates among scholars concerning the legitimacy, permanence, and Shariah compliance of digital assets as charitable instruments. This study aims to examine the legality of cryptocurrency as a potential waqf asset by exploring its compatibility with classical jurisprudential principles and contemporary Islamic financial regulations. A qualitative-deductive methodology was employed, combining doctrinal analysis of fiqh al-mu??mal?t (Islamic commercial law) with comparative evaluation of modern fatwas and regulatory policies issued by national Shariah authorities. The findings reveal that while cryptocurrencies possess economic value (m?l) and transferability, their volatility and speculative nature pose significant challenges to fulfilling the waqf requirement of asset stability and perpetuity (istibq?’ al-?ayn). However, under certain governance mechanisms—such as tokenization backed by tangible or stable assets—cryptocurrency may be conditionally recognized as a legitimate waqf instrument. The study concludes that cryptocurrency’s inclusion in Islamic endowment frameworks is permissible only through rigorous regulatory oversight, ensuring transparency, value preservation, and adherence to Shariah objectives.